Size Dependent Phase Transition in BaTiO3 and PbTiO3: a General Theory Based on a Simple Ising Model - Mikrajuddin Abdullah (Institut Teknologi Bandung, 2004)
A general theory based on simple Ising model has been developed to explain the effect of size on the phase transition in BaTiO3 and PbTiO3. The model can explain very well the presence of critical temperature for the occurrence of tetragonal â cubic structure, the presence of critical size where this transition to occur. Size dependent of the transition is induced by the dependence of dipole-dipole interaction in the sample on the size.